2020
DOI: 10.1101/2020.05.27.20083287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating excess mortality in people with cancer and multimorbidity in the COVID-19 emergency

Abstract: Background: Cancer and multiple non-cancer conditions are considered by the Centers for Disease Control and Prevention (CDC) as high risk conditions in the COVID-19 emergency. Professional societies have recommended changes in cancer service provision to minimize COVID-19 risks to cancer patients and health care workers. However, we do not know the extent to which cancer patients, in whom multi-morbidity is common, may be at higher overall risk of mortality as a net result of multiple factors including COVID-1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
0
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(185 citation statements)
references
References 24 publications
9
155
0
21
Order By: Relevance
“…Historically, it is shown that patients with preexisting heart and lung diseases had a higher mortality rate from SARS 17,[24][25][26][27][28][29] . The same findings have been reported in China 15,16,60 , and United Kingdom 61 . Lippi et al showed that about 20% of hospitalized COVID-19 cases had heart complications as well 16 .…”
Section: Here]supporting
confidence: 88%
“…Historically, it is shown that patients with preexisting heart and lung diseases had a higher mortality rate from SARS 17,[24][25][26][27][28][29] . The same findings have been reported in China 15,16,60 , and United Kingdom 61 . Lippi et al showed that about 20% of hospitalized COVID-19 cases had heart complications as well 16 .…”
Section: Here]supporting
confidence: 88%
“…16,17 Urgent referrals for suspected cancer have fallen in the many countries, 18 which may reflect a decrease in patients presenting with 'red flag' symptoms or changes to clinician thresholds for referral due to health system pressures, leading to both short-and long-term impacts on indirect mortality. 19 Overburdening of the health system and changes to clinical pathways as a response to prioritising COVID-19 cases may leave deficiencies in standard care pathways. 19 Globally, the World Health Organization has found that 42% of countries have experienced disruptions to cancer services, 49% for diabetes and 31% for cardiovascular disease services.…”
Section: Beyond Excess Mortalitymentioning
confidence: 99%
“…19 Overburdening of the health system and changes to clinical pathways as a response to prioritising COVID-19 cases may leave deficiencies in standard care pathways. 19 Globally, the World Health Organization has found that 42% of countries have experienced disruptions to cancer services, 49% for diabetes and 31% for cardiovascular disease services. 20 Concerns about the efficacy of the pandemic response will arise if deaths from COVID-19 are limited only at the expense of deaths from other causes.…”
Section: Beyond Excess Mortalitymentioning
confidence: 99%
“…Emergency department attendance declined by 25% in the week after lockdown was implemented, 3 and data from the Royal College of General Practitioners surveillance system 4 has shown that weekly reported incidence of asthma, intestinal infectious diseases, upper respiratory tract infections, and acute respiratory tract infections was markedly reduced. Substantial reductions in hospital admissions for suspected heart attacks 5 and strokes, 6 and urgent general practitioner (GP) referrals for cancer 7 , 8 have also been reported.…”
Section: Introductionmentioning
confidence: 99%